COMMUNICATIVE APPROACH TO FOREIGN LANGUAGE TEACHING IN THE HIGHER EDUCATION - Lola Teshebaeva (American Journals, 2022)
This article is written about the fact that the meaning of the ideal translation should be clear and natural for the used receptor language forms, and will be devoted to this topic. The following article also provides information on the communicative approach and how it is used in teaching foreign languages.
Keywords: translation, translation competence, lexicon, grammar, communication, communicative approach, analysis and analysis.